‘ACCESSIO AB ALLUVIONE’ I ‘REDITUS VENATIONIS ET AUCUPII’ JAKO ‘FRUCTUS FUNDI’. KILKA UWAG NA MARGINESIE PS. 3,6,22 - Benincasa, Zuzanna (Zeszyty Prawnicze, 2016)
“Accessio ab alluvione” and “reditus venationis et aucupii” as “fructus fundi.” Some Remarks on PS. 3,6,22 Summary The paper examines the controversial text of Pauli Sententiae (PS. 3,6,22), in which the question of considering accessio ab alluvione and reditus venationis et aucupii as a fructus fundi is raised. As defined in Gaius’ Institutiones, an alluvio was an imperceptible deposit of soil upon the bank of the river, the process being so gradual and persistent that no-one could perceive how much was added at any specific moment of time. Since it was inseparable from the native soil of the bank, according to the naturalis ratio such a deposit became the property of the owner of the bank. The author of PS. 3,6,22 explains that such [25] ʽAccessio Ab Alluvioneʼ i ʽreditus venAtionis et Aucupiiʼ 159 a deposit (accessio ab alluvione) did not become the property of the usufructuary of the land since it could not be deemed a fruit obtained from the land (fructus fundi). He treats the potential profits deriving from occasional hunting and fowling on the land given in usufruct in a different manner, because in his opinion they belonged to the usufructuary being fructus fundi. According to the communis opinio, the author of PS. 3,6,22 put together two completely different legal questions as a result of misconstruing Ulpian’s view in D. 7,1,9,4-5. However, a more detailed analysis of texts on accessio ab alluvione and reditus venationis et aucupii shows a connection between the two questions. Accessio ab alluvione and wild animals, birds and fish caught on land subject to usufruct could not be considered fructus fundi, since they were part of nature or the result of a natural process (i.e. the natural action of the river), and their acquisition was only occasional and not frequent. But the usufructuary was allowed to gain profit from hunting on the property given in usufruct and uti frui of the land added by alluvio to the land subject to the usufruct. Accordingly, his gains from hunting and fishing and fruits drawn during the enjoyment of the piece of land added by the natural action of the river were conceived as fructus fundi.